Strategies for conducting Scientific Initiation in times of a pandemic: mitigating losses (Research, Society and Development, 2022)
The present work aimed to point out the strategies adopted for conducting Scientific Initiation in times of pandemic in order to mitigate losses at this challenging time. This is a descriptive, primary, qualitative and reflective study of the experience report type, based on a research project in the area of Veterinary Medicine carried out at IFNMG – Campus Araçuaí. As a result of the COVID-19 Pandemic, the conduction of the research project was replanned in order to maintain the continuity and quality of the research and alleviate the feelings of tension caused by social isolation. The strategies adopted for the research project to be carried out remotely were: Systematic literature review, bioinformatics analysis, construction of the ARACÃO website, development of application prototypes for the rural man. It was extracted from the review that bioinformatics brings the collection of as much biological and statistical information as possible. In the practical activity of bioinformatics, it was possible to elaborate several networks of protein interaction, helping in the investigation of protein signaling pathways, which is one of the specific objectives of the project. Regarding the construction of the website ARACÃO, the experience was very pleasant as it offered ways for the community to participate, reflect and express itself on the social and environmental consequences of the abandonment of domestic animals. The MANZOTEC and FITOVET ONLINE platforms have shown themselves to be technologies that have the potential to motivate the digital transformation in livestock, through the provision of relevant information that supports the decision-making process in rural production activities.